Connes' noncommutative differential geometry and the Standard Model - Várilly Boyle, Joseph C. (1993)
In this paper, the Connes-Lott approach to the phenomenological Lagrangian of the standard theory of elementary particles is reviewed in detail. The paper is self-contained, in that the necessary foundations in noncommutative geometry are fully laid out.